'Doing hymen reconstruction': an analysis of perceptions and experiences of Flemish gynaecologists - Els Leye; Emilomo Ogbe; Maaike Heyerick (BMC, 2018)
Abstract Background Hymen reconstruction (HR) involves the restoration of the hymeneal membrane's gross anatomical integrity. Among the medical profession, hymen reconstruction receives particular attention and its necessity is debated because the surgery is not medically indicated, and often reveals conflicting social norms on virginity and marriageability between health professionals and their patients. The focus of this paper is not to address the many open questions that the ethics and politics around HR reveal, but rather aims at contributing to the much-needed empirical evidence. It presents findings of a study conducted in Belgium (Flanders region), among gynaecologists that aimed at assessing their knowledge, views, and experiences on hymen reconstruction. Methods A digital self-administered questionnaire-based survey was sent to Flemish gynaecologists and trainees in Flanders registered with the Flemish Society of Obstetrics and Gynaecology (VVOG). Results Hundred-and-nine questionnaires were completed. The majority of the respondents (73%) had requests to perform HR. Knowledge and technical skills about HR were considered to be sufficient (69%), even though HR does not seem to be integrated in medical curricula or post-graduate training. Most respondents (72%) would favour the publication of a guideline by their professional organisation. Few respondents discuss alternative options with the patient (19%) and half of the respondents reject to perform HR (49%). The majority of our respondents are against reimbursement of the surgery (70%). Not even half of our respondents believes that a patient is at risk of further violence (47%). 7% of the respondents mentioned complications, but the majority was able to perform a follow up consultation. Conclusions The responses of this survey cannot be generalised to the entire population of gynaecologists in Flanders, but do provide insights in how gynaecologists confronted with HR are approaching such requests, and thus contributes to the empirical evidence. Our paper showed that many Flemish gynaecologist are likely to encounter requests for hymenoplasty, but that a majority would not perform the surgery. There seems to be a lack of guidance and debate in Flanders on the social and moral dimensions of HR, and a number of complexities were revealed when gynaecologists address HR that need further research.